Preliminary verification of the open-source CFD solver SU2 for radial-inflow turbine applications. (September 2017) - Keep, Joshua A.; Vitale, Salvatore; Pini, Matteo; Burigana, Matteo
Abstract: There is a need for reliable CFD tools for design and performance prediction of Organic Rankine Cycle turbines. The open-source solver SU2 has gained recognition in the ORC community for the possibility to efficiently perform analysis and design of devices operating with organic flows. This paper presents a preliminary verification of the open-source tool SU2 for the simulation of organic flows in radial inflow turbines. A comparison is performed against the well established commercial ANSYS CFX solver for two exemplary test-cases. Results show that the solvers predict quantitatively and qualitatively similar fluid-dynamic performance and flow features.